Incidence of Complications of Colostomy in Children with Hirschsprung Disease and Anorectal Malformation: Complications of Colostomy in Children - Haider, Naveed; Rauf, Muhammad; Sulman Butt, Muhammad; Shahbaz, Ferheen; Bilal Afzal, Muhammad; Ullah, Saif; Saleem, Javeria (Pakistan Journal of Health Sciences, 2022)
Colostomy formation, A surgery used in the management of Hirschsprung's disease, and anorectal malformations. colostomy complications were represented both in children with Hirschsprung's disease and in those with anorectal malformation Objective: To estimate the incidence rate of major complications after colostomy formation surgery. Methods: A prospective longitudinal descriptive study was performed to calculate the incidence rates of complications following the surgical intervention of colostomy formation. All 200 cases of consecutive young children (age 2 days to 60 days) who received a colostomy between (date January 2017 to January 2020) were included. The incidence of major colostomy-related complications was calculated. This was analyzed for colostomy formation. Non-colostomy-related complications were not included in study. Results: 200 young children were included. And a follow-up of 6 months of this study to review the complications of colostomy formation in infants and children with Hirschsprung's disease or an anorectal malformation. 80% experienced colostomy-related complications, colostomy prolapse (35% in HD more with a transverse colostomy, 20% in Anorectal malformation), colostomy stenosis (15% in HD, 35% in Anorectal malformation), Skin excoriation (40% in HD, 25% in Anorectal malformation), Revision of colostomy (15% in HD, 12% in Anorectal malformation), colostomy bleeding almost same in both conditions 30%, Parastomal herniation, 5% in both conditions, colostomy wound infection were also recorded, Same in both conditions 5%. Conclusions: Consider the risks associated with a colostomy formation before undergoing surgery in both Hirschsprung's disease and anorectal malformation. complications can be excluded with careful surgery and proper nursing care.